Use of Piaget's theory in preschool nutrition education - Başkale,Hatice (2009)
The preschool period is a time when children learn many concepts and develop life-long habits. In that period, children learn about appropriate and balanced nutrition and acquire good eating habits for later years. Piaget determined that children's cognitive development is important for their understanding of and learning about the world around them. Piaget's theory can be used as a guide in nutrition education. In fact, it helps to design effective nutrition education appropriate for the developmental stages of childhood. The purpose of this article is to describe Piaget's theory and nutrition education based on this theory. This article will discuss how Piaget's theory is to be used in the development of nutritional habits of preschool children and will make an attempt to provide a viewpoint for those who provide nutrition education.